2015
DOI: 10.1097/md.0000000000001716
|View full text |Cite|
|
Sign up to set email alerts
|

Epidemiology, Clinical Features, and Prescribing Patterns of Aortic Aneurysm in Asian Population From 2005 to 2011

Abstract: Aortic aneurysm (AA) is a leading cause of death in Asia and the world. The prevalence in Western countries is around 1.3% to 8%. However, it is still unclear about the incidence, prevalence, and mortality of AA in Asian population. The aim of this study is to investigate the epidemiology of AA for all subtypes in Taiwan, and describe the clinical features and prescribing patterns for AA population.A population-based study was conducted using information from National Health Insurance Research Database (NHIRD)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 27 publications
5
24
0
Order By: Relevance
“…Finally, comparing with epidemiological studies in Western countries, our study showed a relatively low prevalence among Taiwanese population, which was consistent with previous studies from Asian countries (0.3–0.5 %) [30]. However, the prevalence and incident rate in Taiwan NHI database were even lower than reported rates among other Asian countries [30]. The prevalence calculated from diagnosis-specific claim data might be lower than those epidemiological data from the reports of screening programs.…”
Section: Discussionsupporting
confidence: 92%
“…Finally, comparing with epidemiological studies in Western countries, our study showed a relatively low prevalence among Taiwanese population, which was consistent with previous studies from Asian countries (0.3–0.5 %) [30]. However, the prevalence and incident rate in Taiwan NHI database were even lower than reported rates among other Asian countries [30]. The prevalence calculated from diagnosis-specific claim data might be lower than those epidemiological data from the reports of screening programs.…”
Section: Discussionsupporting
confidence: 92%
“…Notably, the risk of AA increases dramatically after 60 years of age [ 1 ]. Patients older than or equal to 75 years predominated in our AA cohort (56.4%), and males accounted for most cases (73.3%), which is consistent with prior studies [ 1 , 14 ].…”
Section: Discussionsupporting
confidence: 91%
“…Data regarding hospital visits, emergency care and prescriptions were provided by the National Health Insurance Research Institutes. The diagnosis of AA in the NHIRD has previously been described 9. This study was approved by the Institutional Review Board of Kaohsiung Medical University Hospital (KMUH-IRB-EXEMPT-20130199).…”
Section: Methodsmentioning
confidence: 99%
“…The diagnosis of AA in the NHIRD has previously been described. 9 This study was approved by the Institutional Review Board of Kaohsiung Medical University Hospital (KMUH-IRB-EXEMPT-20130199).…”
Section: Methodsmentioning
confidence: 99%